Pengaruh pemberian ampas kelapa fermentasi dalam ransum terhadap persentase organ dalam dan lemak abdomen ayam broiler - Fajrin M Samiun; Emy Saelan Emy; Sulasmi (Agrivet : Jurnal Ilmu-Ilmu Pertanian dan Peternakan (Journal of Agricultural Sciences and Veteriner), 2025)
This study aims to determine the effect of adding fermented coconut dregs to rations on the percentages of internal organs and abdominal fat in broiler chickens. The research was conducted in the experimental cage of the Animal Husbandry Study Program at Khairun University, Fitu Village, South Ternate City. This study utilized 80 broilers in a Completely Randomized Design (CRD) comprising four treatments and four replications, with each replication consisting of 5 broilers. The treatments were: R0 (100% commercial feed), R1 (10% fermented coconut pulp + 90% commercial feed), R2 (20% fermented coconut pulp + 80% commercial feed), and R3 (30% fermented coconut pulp + 70% commercial feed). The data obtained were analyzed using one-way Analysis of Variance (ANOVA) and further tests with the Duncan Multiple Range Test (DMRT). The study's results showed that providing fermented coconut dregs in the ration had no significant effect (P > 0.05) on the percentage of internal organs. However, they had a significant effect (P < 0.05) on the percentage of abdominal fat in broilers. It can be concluded that providing fermented coconut dregs up to 20% in the ration does not affect the weight of internal organs, namely the liver, heart, gizzard, and abdominal fat.